Distinguishing Echinococcus granulosus sensu stricto genotypes G1 and G3 with confidence: A practical guide - Kinkar, Liina; Laurimae, Teivi; Acosta-Jamett, Gerardo; Andresiuk, Vanessa; Balkaya, Ibrahim; Casulli, Adriano; Saarma, Urmas (Elsevier, 2018)
Cystic echinococcosis (CE), a zoonotic disease caused by tapeworms of the species complex Echinococcus granulosus sensu lato, represents a substantial global health and economic burden. Within this complex, E. granulosus sensu stricto (genotypes G1 and G3) is the most frequent causative agent of human CE. Currently, there is no fully reliable method for assigning samples to genotypes G1 and G3, as the commonly used mitochondrial coxl and nad1 genes are not sufficiently consistent for the identification and differentiation of these genotypes. Thus, a new genetic assay is required for the accurate assignment of G1 and G3. Here we use a large dataset of near-complete mtDNA sequences (n = 303) to reveal the extent of genetic variation of G1 and G3 on a broad geographical scale and to identify reliable informative positions for G1 and G3. Based on extensive sampling and sequencing data, we developed a new method, that is simple and cost-effective, to designate samples to genotypes G1 and G3. We found that the nad5 is the best gene in mtDNA to differentiate between G1 and G3, and developed new primers for the analysis. Our results also highlight problems related to the commonly used cox1 and nad1. To guarantee consistent identification of G1 and G3, we suggest using the sequencing of the nad5 gene region (680 bp). This region contains six informative positions within a relatively short fragment of the mtDNA, allowing the differentiation of G1 and G3 with confidence. Our method offers clear advantages over the previous ones, providing a significantly more consistent means to distinguish G1 and G3 than the commonly used cox1 and nad1.
Keywords: Cystic echinococcosis; Echinococcus granulosus sensu stricto; Genotype identification; Mitochondrial markers; The nad5 gene